Adoption of improved rice management practices in Southeast Asia - CGIAR Research Program on Rice (2019)
More than 600,000 farmers in China, Indonesia, Myanmar, Sri Lanka, Thailand, and Vietnam have been reached with a variety of improved management practice. These include 'single-technology' options such as improved water management (eg alternate wetting and drying), nutrient management (eg site-specific nutrient management), pest, rodent, and weed control, and including integrated crop management options.